Religious Values into the Character Development Program at Az-Zikri Islamic Elementary School: Cultivating Students' Piety and Social-Emotional Intelligence through Worship and Ethics.s - Fajriah Inayati Jia; Hikma Nurfadila; Yasmin Harahap (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2026)
Islamic education in Indonesia plays a crucial role in shaping the character of the younger generation, particularly at the elementary school level. As technological developments and globalization influence students' mindsets and behavior, it is crucial to explore innovative ways to instill religious values ​​that can foster noble character. This study aims to analyze the development of a religious program at Az-Zikri Islamic Elementary School in Bone Regency, with the goal of shaping students' character through worship and social ethics. This study employed a descriptive, qualitative case study approach. Data collection techniques included in-depth interviews and documentation of religious activities at the school. Data analysis employed the Miles and Huberman model, which encompasses data reduction, data presentation, and conclusion drawing. Key findings indicate that programs such as congregational prayer, memorization (tahfidz), morning dhikr (recitation of the Quran), and Islamic literacy activities successfully improved students' discipline, independence, and social awareness. Furthermore, these religious activities also contributed to the development of more empathetic, respectful, and inclusive social attitudes. The results of this study provide a significant contribution to religious education, demonstrating that structured worship practices can enhance students' religious and social character.